Takotsubo cardiomyopathy in elderly female trauma patients - a case series and mini-review - Patel,V; Levy,S; Malik,I; Fertleman,M; Koizia,L (Journal of Medical Case Reports, 2021)
Takotsubo cardiomyopathy is a syndrome characterised by acute left ventricular wall motion abnormalities leading to left ventricular systolic dysfunction. It remains an important differential diagnosis for acute coronary syndrome. For patients requiring surgical management, delays in the diagnosis of Takotsubo cardiomyopathy may lead to postponement of urgent operative management. This delay in surgery likely impacts on length of hospital stay, leading to an increasing morbidity and mortality. Here we describe three cases of Takotsubo cardiomyopathy occurring in three elderly trauma patients and the impact on their clinical course.